PENERAPAN FOCUSED STIMULATION DALAM KEMAMPUAN BAHASA RESEPTIVE PADA ANAK RETARDASI MENTAL DI RUMAH SAKIT JIWA TAMPAN PEKANBARU - Alucyana A.; Ida Windi W.; Dian T. Utami (Universitas Al-Hikmah Indonesia, 2020)
This study aims to see the application of the Focused Stimulation Method in improving the ability of prescription language in children with mental retardation at Tampan Mental Hospital Pekanbaru. The subjects in this study were 3 people with the criteria of experiencing low mental retardation and prescription language development. The implementation of the Focused Stimulation Method was carried out for 10 sessions, including baseline results and evaluation after implementation. From the results of the application of the method shows an increase in understanding of the receptive language on the subject. This increase can be seen from the baseline and evaluation results. In the FA subject there was an increase, namely the baseline results got 3 points and the evaluation score became 5 points, this means that there was an increase of 2 points. In the FR subject there was an increase, namely the baseline results got a value of 4 points and the evaluation value was 7 points, this means that there was an increase of 3 points. In the FM subject there was an increase, namely the baseline results got 5 points and the evaluation score became 8 points, this means that there was an increase of 3 points. Thus it can be said that the Focused Stimulation Method is effective for improving receptive language in children with mental retardation